Intergroup Contact: An Investigation of Intergroup Contact between Students with Different Social Identities Living in The Same Dormitory Room - Tarkan Kaçmaz; Abbas Türnüklü; Veysel Karazor (Anı Publishing, 2019)
The aim of this research is to provide an in-depth examination of the frequency and quality of intergroup contact among university students with different social identity categories who live in the same dormitory room. The research was designed as a qualitative study utilizing phenomenological approach. A total of 45 students, who identified themselves as Turkish (22) and Kurdish (23), were interviewed and qualitative data were collected through semi-structured interview technique. In the analysis of qualitative data, both content and thematic analyses were performed. The results of the study indicated that the students interacted every day. Majority of the common activities students engaged in at the dormitory included chatting, eating together, academic and sports activities and watching movies; and outside the dormitory building included participating in cultural activities, sitting in cafés, eating out, academic and sports activities, hanging out and shopping. It was determined that the students interacted voluntarily and sincerely, regardless of the difference in social identity. When joint activities were carried out, personality traits were found to be more prominent than ethnic identities. The majority of students from either social identity were found to feel accepted by the other group. Even though the students with either social identity are sincere in their relations with the other group members, they still have a more specific and intense quality of sincerity with the inner group members from their own social identities.